The Effectiveness of Gross Motor Playmat Media on Number Concept Recognition Skills in Children Aged 5–6 Years - Hasanah, Shevia Nidaul; Zultiar, Indra; Poppyariyana, Alfian Ashshidiqi (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2025)
The goal of education in Indonesia is to develop students’ abilities across various domains, one of which is cognitive development. Introducing number concepts is one type of learning that supports cognitive growth. This study aims to examine the effectiveness of using gross motor playmat media. The objectives of the study are to explore the planning, implementation, and learning outcomes related to number concept recognition using gross motor playmat media in Group B students at PAUD SPS Melati III, Nyalindung Subdistrict, Sukabumi Regency. This research employed a qualitative method with a case study design. The subjects of the study were a teacher and the school principal, selected through purposive sampling. Data collection techniques included interviews with the teacher and principal, observation of student activities during the learning process, and documentation such as developmental records and anecdotal notes. The findings show that the use of gross motor playmat media in introducing number concepts to Group B children at PAUD SPS Melati III was considered effective, as indicated by the improved learning outcomes observed after the media was used.